ANALYSIS OF THE EFFECTIVENESS VALUE OF IMPLEMENTING THE TWO-TIER DECEPTION-DRIVEN SECURITY MODEL IN CYBER SECURITY SYSTEMS - Sahrul Ramadhan; Agung Budi Sutanto; Arya Adhyaksa Waskita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The increasing complexity of cyber attacks, especially Brute Force and SQL Injection, poses a significant risk to production environments. Conventional reactive security measures are often unable to provide sufficient understanding regarding the behavior of attackers. This study designs and analyzes a